2012
DOI: 10.1088/0953-8984/24/28/284129
|View full text |Cite
|
Sign up to set email alerts
|

Active Brownian motion tunable by light

Abstract: Active Brownian particles are capable of taking up energy from their environment and converting it into directed motion; examples range from chemotactic cells and bacteria to artificial micro-swimmers. We have recently demonstrated that Janus particles, i.e. gold-capped colloidal spheres, suspended in a critical binary liquid mixture perform active Brownian motion when illuminated by light. In this paper, we investigate in more detail their swimming mechanism, leading to active Brownian motion. We show that t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
490
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 355 publications
(513 citation statements)
references
References 40 publications
16
490
0
Order By: Relevance
“…The emergence of arrested phase owing to density-dependent mobility has been discussed theoretically in the context of bacteria by Tailleur & Cates [58]. The role of the self-trapping mechanism for the emergence of clustering was shown in the recent and remarkable experiments by Buttinoni et al [59], where they used 'large' 4 μm self-propelled carbon-coated Janus colloids, which self-propel under illumination in a near-critical water-lutidine mixture [60], and for which the caps can be optically resolved, indicating the direction of self-propulsion. They showed that the particles in a clusters are arrested, heads-on.…”
Section: (C) Results and Discussionmentioning
confidence: 99%
“…The emergence of arrested phase owing to density-dependent mobility has been discussed theoretically in the context of bacteria by Tailleur & Cates [58]. The role of the self-trapping mechanism for the emergence of clustering was shown in the recent and remarkable experiments by Buttinoni et al [59], where they used 'large' 4 μm self-propelled carbon-coated Janus colloids, which self-propel under illumination in a near-critical water-lutidine mixture [60], and for which the caps can be optically resolved, indicating the direction of self-propulsion. They showed that the particles in a clusters are arrested, heads-on.…”
Section: (C) Results and Discussionmentioning
confidence: 99%
“…The authors studied the swimming behavior of the Janus particles in the patterned surroundings and demonstrated the steering capability with the arranged obstacles. Buttinoni et al [35] continued this study and showed a good direction control by changing the intensity of the green laser beam, which was used to generate the temperature difference in the Janus particle. The particle moved into the high light intensity area with the speed up to 0.7 μm/s.…”
Section: Propulsion By Active Brownian Motion and Self Thermophoresismentioning
confidence: 89%
“…Among the chemical micro swimmers, even though there are still debates on the mechanism [27], some devices utilize the bubble recoiling method to make momentum transfer by inertia propulsion [28][29][30][31]. The electric and thermophoresis methods may be categorized as viscous propulsion, as the active Brownian motion method may [32][33][34][35].…”
Section: Propulsion In Micron and Nano Scalementioning
confidence: 99%
“…Illumination of the sample with visible laser light leads to absorption and subsequent heating of the carbon coating. When the temperature of the coating exceeds T C , the binary liquid becomes locally demixed, which leads to propulsion of the particle by self-diffusiophoresis [18,19]. For the illumination intensities I used in this work, the propulsion velocity v linearly increases with I [ Fig.…”
Section: A Experimental Setupmentioning
confidence: 99%
“…1(b)] above a threshold value I = 0.28 W/mm 2 . Below this value, the light intensity is not sufficient to induce demixing and no active motion is observed [18]. As the illumination source, we used a diode-pumped laser with wavelength λ = 532 nm.…”
Section: A Experimental Setupmentioning
confidence: 99%